2000
DOI: 10.4049/jimmunol.165.2.813
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Nonanaphylactogenicity of a Monoclonal Anti-IgE Antibody

Abstract: IgE Abs mediate allergic responses by binding to specific high affinity receptors (FcεRI) on mast cells and basophils. Therefore, the IgE/FcεRI interaction is a target for clinical intervention in allergic disease. An anti-IgE mAb, termed BSW17, is nonanaphylactogenic, although recognizing IgE bound to FcεRI, and interferes with binding of IgE to FcεRI. Thus, BSW17 represents a candidate Ab for treatment of IgE-mediated disorders. By panning BSW17 against random peptide libraries displayed on phages, we define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(27 reference statements)
0
11
0
2
Order By: Relevance
“…Functional anti-IgE antibodies such as omalizumab have been previously shown to recognize identical or overlapping epitopes with those of FcRI␣ [53][54][55][56] in the C3 domain of IgE, thereby being able to prevent the interaction of IgE and FcRI␣ initiating mast cell and basophil triggering. Thus, the capacity of the selected DARPins to react with the functionally active C3 domain of IgE was tested in a competition experiment using SPR.…”
Section: Epitope Mapping By Sprmentioning
confidence: 99%
“…Functional anti-IgE antibodies such as omalizumab have been previously shown to recognize identical or overlapping epitopes with those of FcRI␣ [53][54][55][56] in the C3 domain of IgE, thereby being able to prevent the interaction of IgE and FcRI␣ initiating mast cell and basophil triggering. Thus, the capacity of the selected DARPins to react with the functionally active C3 domain of IgE was tested in a competition experiment using SPR.…”
Section: Epitope Mapping By Sprmentioning
confidence: 99%
“…7 The murine anti-human IgE mAb used for construction of the bsc-IgE/CD3 antibody derivative was itself nonanaphylactogenic and had been analyzed in detail by mapping the relevant epitopes to isolated Cε3 and Cε4 of the IgE molecule, a conformational epitope apparently inaccessible on IgE when bound to its Fc receptors. 8 Nevertheless, we carefully examined whether the bscIgE/CD3 antibody construct is indeed free of any anaphylactogenic properties and devoid of any bystander cytotoxic activity in the presence of preactivated human T cells. Accordingly, we demonstrated that cells that bound soluble IgE either through the high-affinity FcεRI or the low-affinity FcεRII (CD23) were not affected by prestimulated CD8 1 T cells, even at high concentrations (1 mg/mL) of the bsc-IgE/CD3 antibody (Fig 2, A and B, and see Fig E3 in this article's Online Repository at www.jacionline.org).…”
Section: To the Editormentioning
confidence: 99%
“…The site on human IgE responsible for binding to FcεRI has been associated with the Cε2, Cε3, and Cε4 domains by binding inhibition studies involving recombinant IgE truncations [5,6], chimaeric IgE [7], site-directed mutagenized IgE [8,9], synthetic peptides corresponding to IgE Fc domains and antibodies induced by such peptides [10][11][12][13][14], and mimetope peptides [9,15]. These observations pointed to a highly conformational receptor binding site that has recently been solved by resolution of the crystal structure of a human IgE-FcεRI complex.…”
Section: Introductionmentioning
confidence: 99%
“…These do not cross-link FcεRI-bound IgE and so they do not trigger degranulation and anaphylaxis [15,17,18]. Two of these antibodies are in clinical trial, and passive immunizations have provided desensitisation for patients with allergic rhinitis and allergic asthma [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%